Best Practice Through Broken Triangle, Square and Heart Can Grow Constitutional Awareness and Increase Citizenship Values: Best Practice Melalui Broken Triangle, Square dan Heart Dapat Menumbuhkan Kesadaran Berkonstitusi dan Meningkatkan Nilai Kewarganegaraan - Fatimah, Siti (Pedagogia : Jurnal Pendidikan, 2022)
This Best Practice is the best experience in learning to increase awareness about constituting and improving learning outcomes through the Broken Square Triangle, Square, and Heart model in Class VIII E of SMP Negeri 2 Wonosari Gunungkidul in the Even Semester of the 2019/2020 Academic Year. The results of the teacher's observations during PBM, students like to littering, wearing colorful shoes, long hair, unidentified uniform at SMPN 2 Wonosari, less respect for teachers in class, not concentrating on teaching and learning activities, sleeping in class. After studying with the Broken Triangle, Square and Heart models, there is a change in constitutional awareness, as evidenced by the research data. At the first meeting with the lecture method, the violation was 18.89%. When KBM uses the Broken Triangle, Square and Heart model, in the second meeting there is a violation of 2.59% and the third meeting there is a violation of 1.48%. This has proven to be an increase in constitutional awareness. From the learning outcomes, the lecture method shows an average result of 59.47, with the Broken Triangle, Square and Heart model, an average of 66.0 and 86.13. Thus, it shows that the Broken Triangle, Square and Heart models are more effectively used in PPKn learning.